Service enterprise integration : an enterprise engineering perspective - Hsu, Cheng, 1951- (New York : Springer, 2007)
Service Enterprise Integration is developing a business paradigm that is of considerable interest in both the'push' research the academic area and the'pull' research of industry. A prominent example of this development has been the transformation of IBM into a service enterprise and the labeling of its new business model as'On-Demand Business.' Manufacturing research and practice have done considerable work on the problem of service productivity. In fact, this work has extended the operations of many manufacturing firms to include the'service enterprise' component. IBM, GE, Siemens are several examples of this development. The book investigates the proven concepts, models, methods, and techniques in manufacturing operations and examine all their aspects that are relevant to the problem of service productivity. The presentations provide literature reviews, conceptual analysis, and solution-result-oriented applications on topics including ontology, reference models, ERP, supply chain integration, knowledge management, data security, and a variety of cases on particular applications
From just in time manufacturing to on-demand services / Ananth Krishnamurthy -- Services innovation: decision attributes, innovation enablers, and innovation drivers / James M. Tien -- Reengineering the organization with a service orientation / Fran's B. Vernadat -- Customer incentives in time-based environment / Jian Chen and Nan Zhang -- Auctions as a dynamic pricing mechanism for e-services / Juong-Sik Lee and Boleslaw K. Szymanski -- A framework for service enterprise integration: a case study / Mark E. Dausch -- Continuous evaluation of information system developments / Ming-Chuan Wu -- Models of cyberinfrastructure-based enterprises and their engineering / Cheng Hsu.
Includes bibliographical references and index
Keywords: Service industries -- Information technology; Service industries -- Technological innovations; Information technology -- Management; New business enterprises -- Management -- Decision making; Management information systems; Knowledge management